The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/rcm.3170
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and evaluation of dechlorination processes using compound‐specific chlorine isotope analysis

Abstract: A simple, quick and sensitive method for the compound-specific stable chlorine isotope analysis of chlorinated solvents by conventional quadrupole gas chromatography/mass spectrometry (GC/MS) is presented. With this method, compound-specific stable chlorine isotope ratios of typical chlorinated solvents like tetrachloroethene (PCE) and trichloroethene (TCE) can be determined quantitatively within 30 min by direct injection. The chlorine isotope ratios of target substances are calculated from the peak areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 29 publications
1
105
0
1
Order By: Relevance
“…Instead the GC effluent is transferred directly to a high-precision IRMS (Fig. 4 upper panel) [99] or a quadrupole MS [100][101][102]. Instead of species that contain only one chlorine atom (e.g., 37 [101,102], fragment ions [6,99], or a weighted combination of both [100].…”
Section: Online High Temperature Conversion (Htc) Convertsmentioning
confidence: 99%
“…Instead the GC effluent is transferred directly to a high-precision IRMS (Fig. 4 upper panel) [99] or a quadrupole MS [100][101][102]. Instead of species that contain only one chlorine atom (e.g., 37 [101,102], fragment ions [6,99], or a weighted combination of both [100].…”
Section: Online High Temperature Conversion (Htc) Convertsmentioning
confidence: 99%
“…achieved continuous flow analysis by coupling a gas chromatograph to an IRMS instrument, but their method suffers from the need to specifically adjust the Faraday cups for each compound . An attractive online method was conceived by Sakaguchi‐Söder, Aeppli, and colleagues using gas chromatography coupled to quadrupole mass spectrometry (GCqMS) . However, their method involves substantial calculation to obtain isotope ratios from compound‐specific mass spectrometric data and demands repeated comparison with molecularly identical reference compounds .…”
Section: Chlorine Isotope Analysismentioning
confidence: 99%
“…Several studies have indicated that a dual element isotope approach has the potential to distinguish different transformation pathways Elsner et al, 2005;Fischer et al, 2008;Elsner, 2010). However, analytical methods for dual element isotope analysis of 13 C/ 12 C and 37 Cl/ 35 Cl of chlorinated ethenes have only relatively recently become available and are still being improved (Shouakar-Stash et al, 2005;Sakaguchi-Söder et al, 2007;Bernstein et al, 2011;Aeppli et al, 2010;Jin et al, 2011). Abe et al (2009) were the first to apply dual element (C, Cl) isotope fractionation to distinguish between microbial aerobic oxidation and microbial anaerobic reductive dechlorination of cis-DCE and VC.…”
Section: Introductionmentioning
confidence: 99%